Benzoxaborole as a new chemotype for carbonic anhydrase inhibition. Issue 80 (19th September 2016) - Alterio, Vincenzo; Cadoni, Roberta; Esposito, Davide; Vullo, Daniela; Fiore, Anna Di; Monti, Simona Maria; Caporale, Andrea; Ruvo, Menotti; Sechi, Mario; Dumy, Pascal; Supuran, Claudiu T.; Simone, Giuseppina De; et al.
Abstract : In this paper we provide the first experimental evidence that benzoxaboroles can be used as CA inhibitors. Abstract : In this paper we report the synthesis of a series of benzoxaborole derivatives, their inhibition properties against some carbonic anhydrases (CAs), recognized as important drug targets, and the characterization of the binding mode of these molecules to the CA active site. Our data provide the first experimental evidence that benzoxaboroles can be efficiently used as CA inhibitors.